2005
DOI: 10.1021/es051213x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Mass Inventory of Total Dichlorodiphenyldichloroethylene in the Water Column of the Southern California Bight

Abstract: A large-scale survey on the area and depth stratified distribution of dichlorodiphenyltrichloroethane (DDT; mainly p,p'- and o,p'-dichlorodiphenyldichloroethylene (DDE)) contamination in the water column of the Southern California Bight (SCB) was conducted in 2003-2004 using a solid-phase microextraction-based sampling technique. Dissolved-phase DDEs were clearly widespread, with the central SCB containing the highest levels, and the Palos Verdes Shelf sediments have remained the dominant source of DDT compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
5
17
0
Order By: Relevance
“…3), and this was also true for most samples during the deposition event. The results were consistent with that obtained in the field reported by some researchers (Ko and Baker, 1995;Luo et al, 2004;Zeng et al, 2005); they found that there was significant difference in total/freely dissolved HOC concentrations between the surface water and bottom water. Fernandez et al (2012) reported that the freely dissolved concentrations of DDT congeners in the bottom water were approximately six times higher than those in the surface water in the vicinity of a marine superfund site on the Palos Verdes Shelf.…”
Section: Total and Freely Dissolved Pah Concentrationssupporting
confidence: 92%
“…3), and this was also true for most samples during the deposition event. The results were consistent with that obtained in the field reported by some researchers (Ko and Baker, 1995;Luo et al, 2004;Zeng et al, 2005); they found that there was significant difference in total/freely dissolved HOC concentrations between the surface water and bottom water. Fernandez et al (2012) reported that the freely dissolved concentrations of DDT congeners in the bottom water were approximately six times higher than those in the surface water in the vicinity of a marine superfund site on the Palos Verdes Shelf.…”
Section: Total and Freely Dissolved Pah Concentrationssupporting
confidence: 92%
“…Since the entire amount on the SPME fiber is introduced into the GC or HPLC column, good sensitivity is attained. The use of injector-type SPME to measure C free and related parameters is an extension of the originally intended application (Leslie et al, 2002ab; Maruya et al, 2009; Ramos et al, 1998; Xu et al, 2007; Yang et al, 2006, 2007; Zeng et al, 2005). Due to its assembly configuration, the operation of injector-SPME can be operated with an autosampler, which maximizes sample throughput and precision, but also restricts the sampling time to be within the range of minutes and up to one hour.…”
Section: Passive Samplers For Measuring Freely Dissolved Concentramentioning
confidence: 99%
“…4). The observed pattern for DDTs is likely explained by the location of the Palos Verdes Shelf Superfund Site, which lies~23 km west of Bolsa Chica in the northern area of the SCB (Fry, 1994;Schiff and Allen, 2000;Zeng et al, 2005). While many seabird populations have recovered as contaminant exposure has declined, DDT levels remain detectable in coastal wildlife in the SCB (Macintosh et al, 2016).…”
Section: Detecting Toxicant Trends In Space and Timementioning
confidence: 99%
“…Numerous other toxicants, including mercury (Hotham and Powell, 2000;Komoroske et al, 2012), selenium (Ohlendorf et al, 1985;Hotham and Powell, 2000), arsenic (Komoroske et al, 2011), PCBs (polychlorinated biphenyls, e.g. industrial and electrical byproducts, Fry, 1995, Schiff and Allen, 2000, Brown et al, 2006, Jarvis et al, 2007, PBDEs (polybrominated diphenyl ethers, e.g., flame retardants, Brown et al, 2006) and CHLs (chlordanes, Ohlendorf et al, 1985, Schiff andAllen, 2000), have also been detected in wildlife, sediments, and waters (Zeng et al, 2005;Dodder et al, 2012) in the SCB. Although seabirds have been recognized as sentinels of marine systems (e.g., Burger and Gochfeld, 2002;Elliott and Elliott, 2013), most contaminant monitoring efforts have yet to include seabirds as part of the typically studied samples, a list that often includes water, sediment, bivalves, and fish (e.g., Zeng et al, 2005;Parnell et al, 2008;Dodder et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation